The Making of the Gdańsk Metropolitan Region. Local Discourses of Identities, Powers, and Hopes - Czepczyński, Mariusz (Quaestiones Geographicae, 2014)
The process of metropolitanisation of the Gdańsk area is facilitated by public discourse involving local and regional politicians, media, and inhabitants. The discussion is based upon historical narrations, but also local ambitions, hopes and emotions, as well as infrastructural projects and investment attractiveness. Foucault suggests that modern power is a dispersed set of micro-practices, many of which operate through the normalising gaze of surveillance regimes. Gdańsk metropolitan cooperation, competition and encounters make the core of the paper; local and regional unifying initiatives and processes are accompanied by examples of separatism, identity conflicts, and political disagreements